Urban safety: a re-reading of the sense of unsafety through individual and ecological dimensions - Ferretti, Fabio (European journal of criminology, 2019)
The issue of urban safety is a research topic that has attracted the attention of scholars for several years, particularly in relation to the effects of individual and environmental variables that influence the fear of crime. Some recent studies have redefined the study of fear of crime, widening it to a more general dimension represented by the perception of safety. However, no specific tool has been proposed to measure this construct. In this paper, a new assessment scale of the perception of unsafety has been used to examine the impact of individual factors (gender, age, etc.) and ecological factors (ethnic composition of the neighbourhood, residential stability, etc.) on the dimensions of the scale (general sense of unsafety, perception of physical and social disorder, collective efficacy perception and preoccupation with crime). Results showed a strong convergence with the existing evidence with regard to the ambiguous role of some individual variables, such as gender and age, and for the influence of the characteristics of the neighbourhood.